1990
DOI: 10.1128/iai.58.7.2386-2388.1990
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that endogenous gamma interferon is produced early in Listeria monocytogenes infection

Abstract: It has been presumed that gamma interferon (IFN-gamma), which plays an essential role in antilisterial resistance, is produced late in Listeria monocytogenes infection. In the present study, however, IFN-gamma was detected in the bloodstreams and spleens of mice from days 1 to 4 of L. monocytogenes infection by both a double-sandwich enzyme-linked immunosorbent assay and an immunohistochemical technique, suggesting that endogenous IFN-gamma is produced early but not late in L. monocytogenes infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 15 publications
4
26
0
2
Order By: Relevance
“…There are only a few reports on the kinetics of endogenous IFN-7 production during infections. In listerial infection, endogenous IFN-y production coincided with bacterial growth (Nakane et al, 1990). Our present data also indicate that endogenous IFN-y production coincides with the viral replication (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There are only a few reports on the kinetics of endogenous IFN-7 production during infections. In listerial infection, endogenous IFN-y production coincided with bacterial growth (Nakane et al, 1990). Our present data also indicate that endogenous IFN-y production coincides with the viral replication (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…IFN-y assay of the tissue homogenate was carried out by a double-sandwich enzyme-linked immunosorbent assay (ELISA) as previously reported (Nakane et al, 1990). Rat anti-mouse IFN-y mAb (R4-6A2) purified by DEAE Affi-Gel Blue column chromatography (Nakane et al, 1989) was used as a capture antibody.…”
Section: Ifn-t Assaymentioning
confidence: 99%
“…It is known that IFN-7, by activating macrophages, plays an important role in host defense against many bacteria [reviewed by Murray, 19]. IFN-7 was produced in the early phase of listerial infection in mice [20]. Blanchard et al reported that in vitro production of IFN-7 from mouse splenocytes could be detected as early as 6 h after stimulation with the L. pneumophila antigen, continued to increase for up to 24 h after stimulation and thereafter almost completely ceased [13].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-3, assay in the tissue homogenate was carried out by a double-sandwich enzyme-linked immunosor-bent assay (ELISA) as previously reported (Nakane et al, 1990). Rat anti-mouse IFN-~/ mAb (R46A2) (Spintalny and Havell, 1984) purified by DEAE Affi-Gel Blue Column chromatography was used as a capture antibody.…”
Section: Fn-3 Assaymentioning
confidence: 99%
“…Rat anti-mouse IFN-~/ mAb (R46A2) (Spintalny and Havell, 1984) purified by DEAE Affi-Gel Blue Column chromatography was used as a capture antibody. Rabbit anti-mouse IFN-y serum was obtained from a rabbit hyperimmunized with purified recombinant mouse IFN-3, as that described previously (Nakane et al, 1990). All ELISAs were run with recombinant mouse IFN-7 that was produced and purified by Genentech, Inc. (San Francisco, CA).…”
Section: Fn-3 Assaymentioning
confidence: 99%